The neoliberal discourse of crhoy.com against the operation and funding in Costa Rican public universities - Bustos Mendoza, Nelson Ivan (2021)
The current investigation addresses eight news published by the digital newspaper crhoy.com between October, 2018 and June, 2020. The objective of this research is to analyze, through CDA as theoretical tool, the position and the ideological discourse of these news regarding the resources’ management, the funding, and the expenses in Costa Rican public universities. In order to conduct this study, a qualitative methodology that employs the synthetic phase of discursive strategies recommended by the researcher Neyla Pardo was required. Moreover, Teun Van Dick’s macroproposition methodology and the lexicon suppression method employed by David and Mayer were also fundamental to carry out this investigation. The outcomes of this research lead to conclude that crhoy.com’s news embodies a neoliberal ideology which obeys to political and economic interests whose ultimate purpose is to discredit the image, operation, and contribution of public universities. Furthermore, it can be concluded that crhoy.com suppresses and manipulates the information in its news showing lack of objectivity and neutrality in its journalistic duty.